Implementasi Sistem Monitoring Deteksi Hujan dan Suhu Berbasis Sensor Secara Real Time - Muhamad Yusvin Mustar; Rama Okta Wiyagi (Semesta Teknika, 2017)
The aim of this research is to provide the design and implementation of a monitoring system which is able to detect rain and temperature based on real time sensor. This system focuses on the results of raindrop detection sensor as a rain detector and NTC thermistor as a temperature detector. Both of the sensors have an analog output. Therefore, they require an Analog Data Converter (ADC) to measure. Several tools are used to build this monitoring system, including microcontroller Arduino NANO for input sensor value readings, data processing and programming. Real Time Clock (RTC) is used to provide time information when the sensor works, as well as the telemetry as the wireless communication device. An interface based on Graphical User Interface (GUI) using JAVA as the monitoring software which can be operated on a PC or laptop. Based on the analysis and evaluation, this tool can detect rain and temperatures in real time.